Family related factors and their relationship to the academic performance of second year nursing students - Bunag, Christyn; delos Santos, Reina Rose.; Jacinto, Cecille; Lomboy, Michelle; Moreno, Juan Carlos; Relano, Jannette; Sison, Michelle (Manila College of Nursing University of the Philippines Manila, 2003)
As students enter college life, a lot of adjustments are to be made in order for them to adapt to the very challenging call of the academe. For them, to adjust successfully, support systems must be established to solidify their self-confidence and psychological well- being in dealing with the various factors affecting their studies.

As the most vital support system, family’s role in a student's quest for academic excellence must be well emphasized. This is because any problem in the familial conditions will most likely be reflected in the performance of the students. This study's ultimate goal is to identify family related factors that affect the academic performance of nursing students with the sophomores as the sample. This will help the researchers and other nursing students to be aware of the fact that not everyone of them are going through the same process of life and proper support and understanding should be given to their colleague.

The objectives of the study are the determination of family related factors affecting academic performance of second year nursing students and the determination the relationship between family related factors and academic performance of second year nursing students.

The researchers used descriptive survey design. A questionnaire was distributed to 97 2" year nursing students, 22 males and 75 females. Using the Chi Square test, an association between these variables, family related factors and academic performance, turned out to be significant. However, not all variables compared were significant.

Based on the result of statistical test, type of neighborhood and family structure greatly affected academic performance of students. Although most of them live in a subdivision or village (63 out of 97), statistics show that these students tend to have failing grades.

Aside from the type of neighborhood, family structure shows significant result in relation to arts/sciences and overall subjects. More respondents who have extended family structure had failed subjects compared to those who belong to nuclear family.

Results of Chi Square test for type of student and those who have immediate family member/s working abroad revealed significant statistical finding. Most regular students (43 out of 97) have family members who are not working abroad.
Research (In partial fulfillment of the requirements in the course N199: Nursing Research) -- University of the Philippines Manila, April 2003.
Keywords: Nursing -- Research